Pessoas com neoplasias malignas: curso de vida, identidade e trabalho - Alt, Luciano Luiz (2017)
The labor, as a human activity, permeates the most diverse societies, being an element of inclusion of the man in various aspects, holding their own senses for the individual, contributing to his subjectivity and construction. On sustaining oneself and his dependents, the independence of the subject, the feeling of belonging to a group, feeling useful and having goals in life motivates the human being in his relation to the labor activity. Due to the dynamics of the changes in the man-work relationship and in the context of the current technical and scientific evolution, issues that were little discussed at other times emerge, for example, work for cancer patients during or after treatment and social protection against the vulnerability of cancer. Therefore, the themes to be worked arise: the relationships between individuals affected by cancer with their work, their identity issues, life course, sense of control and normality of life by means of work, besides the vulnerabilities to which those affected by cancer are exposed and the spectrum of social protection to them. The purpose of the dissertation is to know the worker's perceptions about his labor activity, in his life course, in the face of the diagnosis of cancer, contextualizing the illness in and for the work and the relations with the senses expressed in his ways of life, as well as to check how the diagnosis of cancer and its therapies interfere with these perceptions. For this purpose, were performed individual interviews and focus group interviews to capture the sense nuclei wich make up the content of the information. From the research, two papers were elaborated. The first, concluding that work plays a fundamental role on the identity of the cancer patient, as well as in their perception of control and normality of life. The second, that there are social vulnerabilities of cancer patients and that the social protection of the worker, during and after illness is often in deficit.